A study of modifiable factors associated with health‐related quality of life in long‐term cervical cancer survivors. (23rd January 2023) - Dahl, Alv A.; Bentzen, Anne Gry; Fosså, Sophie D.; Hess, Siri Lothe; Kiserud, Cecilie E.
Abstract: Introduction: Health‐related quality of life (HR‐QoL) in cancer survivors is relevant for symptom relief and optimal care. The aim of this cross‐sectional study of long‐term cervical cancer survivors was two‐fold: (a) To compare HR‐QoL in long‐term cervical cancer survivors with reference data; and (b) to identify modifiable factors significantly associated with low levels of generic cancer HR‐QoL in long‐term cervical cancer survivors using high HR‐QoL as reference. Material and methods: Women treated for cervical cancer from 2000 through 2007 who were cancer‐free and alive in 2013 received a mailed questionnaire including scales for anxiety, depression, and HR‐QoL. To obtain a homogeneous sample only women with FIGO stages 1 and 2 were included. The questionnaire included the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire.C‐30 (EORTC QLQ C‐30) for generic HR‐QoL. Groups with high and low HR‐QoL were defined by the median score on the general HR‐QoL item. Between‐group differences were examined with descriptive statistics. Logistic regression analyses examined independent variables associated with low generic HR‐QoL. Results: Complete C‐30 scores were delivered by 472 long‐term cervical cancer survivors. Median age at survey was 53 (interquartile range 14.9) years, and median time since diagnosis was 11 (interquartile range 3.9) years. The proportion of survivors with stage 1 disease was 83% and stage 2 was 17%. Mean generic HR‐QoL scores showed minor differences between long‐term cervical cancer survivors and reference data. In the multivariable analysis, only modifiable variables remained significantly associated with low generic HR‐QoL namely self‐rated health, probable depression, fatigue, and pain. In bivariate analyses other modifiable variables also showed significant associations with low generic HR‐QoL like probable anxiety disorder, obesity, smoking, sleep disturbances, and bowel symptoms. Conclusions: Clinicians should be aware that generic HR‐QoL in long‐term cervical cancer survivors eventually may be improved by identification and treatment of modifiable factors through the whole follow‐up period. Abstract : Health‐related quality of life might eventually be improved by identification and treatment of mental distress, pain and, fatigue in long‐term survivors of cervical cancer.